Agriculture and environmental degradation in Africa: The role of income - Olanipekun, Ifedolapo O.; Olasehinde-Williams, Godwin O.; Alao, Rasheed O. (Elsevier, 2019)
The interconnectivity between environmental degradation, poverty and agriculture is an issue of great concern, especially in developing countries. This paper studies the effect of agriculture on the environment, conditional upon the level of income in a panel of eleven Central and West African countries for the period 1996 to 2015, using Pooled Mean Group (PMG), Mean Group (MG) and Augmented Mean Group (AMG) techniques. Our findings indicate that individually, income and agriculture aggravate environmental degradation. The interaction effect confirms that rising income levels dampen the negative impact of agriculture on the environment. Also, while increased use of renewable energy and improved regulations lower environmental degradation, population growth does more damage to the environment. This study condudes that unsustainable agricultural practices degrade the environment and poverty alleviation can mitigate the effect. To solve the problem of environmental degradation, poverty must be addressed and income levels must be raised in an ecofriendly manner. (C) 2019 Published by Elsevier B.V.
Keywords: Environmental degradation; Agriculture; Poverty; Pooled mean group; Panel causality